THE CONCEPT OF MARITAL SUSTENANCE ACCORDING TO CLASSISCAL AND CONTEMPORARY FIQH BOOKS - Yono, Yono; Muttaqin, Ahsan Imam (IBN KHALDUN BOGOR, 2024)
Marriage will raise various rights and obligations between husband and wife. Among the many rights of the wife and the obligations of the husband, one of them is sustenance. Based on the annual report of the Religious Court, economic factors (material sustenance) are more dominant as a factor causing divorce than other factors. This study aims to determine the concept of sustenance according to classical and contemporary fiqh books, and what are the similarities and differences in the concept of sustenance brought by the two books. This study uses a comparative-descriptive approach method with a type of researchincluded in the library research category. The results of this study indicate that the concept of sustenance between classical and contemporary books does not substantially have many differences, contemporary scholars still refer to the opinions or fiqh books by classical scholars, only there is an expansion of the description of the value of sustenance due to changes in the times and the needs of life. One of the differences is regarding the level of sustenance given, according to classical books, it must be adjusted to the adequacy of the recipient and the ability of the giver. Besides, according to contemporary books, it must be adjustedto the customs that already apply in the place of residence. This research has not referred to more specific books in each school of thought. In the future, research can be carried out that focuses on each school of thought.